The Effect of Exercise Methods and Eye-Foot Coordination on Football Passing Accuracy - Prasetyo, Kukuh; Soegiyanto, Soegiyanto; Irawan, Fajar Awang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The purpose of this study was to find out and analyze: Analyzing the influence between the passing practice of the fixed target and passing target the targeted shifted to the accuracy of passing the football. Analyzing the effect of high and low spy coordination on soccer passing accuracy. Analyzing the interaction of training methods and eye-foot coordination on football passing accuracy. This study uses an experimental method with a 2x2 factorial design, data analysis techniques using Analysis of Variants (ANOVA) at the significance level (Î± = 0.05). The populations in this study were the Garuda Perkasa U-15 players in Pemalang Regency in 2019 totaling 36 players. The sampling technique used purposive sampling with a total sample of 24 players. The results of this study: There is a difference in influence between the passing practice of the fixed target and the passing target of the moving target towards football passing accuracy with the value of sig = 0.039 < Î± = 0.05 and Fvalue = 4.800 > Ftable = 0.504. There is a difference in influence between high and low spy coordination on football passing accuracy where sig = 0.001 < Î± = 0.05 and Fvalue = 3.554 > Ftable =0.504. There is an interaction between the training method and eye-foot coordination on football passing accuracy with sig = 0.014 > Î± = 0.05 and Fvalue = 7.289 > Ftable = 0.504. The conclusions of this study are: There is a difference in influence between the passing practice of the fixed target and the passing target to move towards the accuracy of passing the football. There is a difference in influence between the accuracy of passing football of players who have coordination between high and low ankles. There is an interaction between the training method and eye-foot coordination on football passing accuracy.